Shared Experience Organizational Culture and Ethos at the U.S. Marine Corps Basic School, 1924-1941 - Mazzara, Jennifer L. (Marine Corps University Press (MCUP), 2023)
From early in the modern history of the Marine Corps, The Basic School (TBS) has played an enormously important role in acculturating Marine officers in the profession of arms. Author Jennifer Mazzara's exhaustive and detailed research, which included examining the curricula of prewar TBS, shows that the TBS product, the Marine lieutenant, was fundamental to the early victories of the Second World War. As the only basic-level post-commissioning school in the United States that imparts a generalist education, rather than specialist training, TBS is unique among the military schools operated by the U.S. armed forces. Its distinctiveness stems from two primary features: its structure, and what it provides to its graduates. This history reveals TBS's essential qualities during the interwar period, but it also illuminates the timeless and immutable reality and necessity of this institution that has bound generations of Marine officers to each other and to the Corps.